Predictability of tunnel depth for intrastromal corneal ring segments implantation between manual and Femtosecond laser techniques - Monteiro, Tiago (2018)
To compare the predictability of intrastromal tunnel depth creation for intrastromal corneal ring segments (ICRS) implantation between manual dissection and femtosecond laser using a high-resolution anterior segment optical coherence tomography (AS-OCT). PURPOSE: To compare the predictability of intrastromal tunnel depth creation for intrastromal corneal ring segments (ICRS) implantation between manual dissection and femtosecond laser using a high-resolution anterior segment optical coherence tomography (AS-OCT). METHODS: This multicenter study included patients with keratoconus who had Ferrara-type ICRS implantation at Hospital de Braga using manual dissection and at the Fernandez-Vega Ophthalmological Institute using the femtosecond laser technique. The intended depth of implantation was compared to the achieved postoperative ICRS depth of each case, measured using a swept-source AS-OCT (CASIA SS-1000; Tomey Corporation, Nagoya, Japan) at three points (proximal, central, and distal end of the implant). RESULTS: The study included 105 eyes in the manual group and 53 eyes in the femtosecond laser group. The differences of the intended versus the achieved depth were statistically higher in the manual group for all positions measured (Wilcoxon ranked-sum, P < .001). In the manual group, there were significant differences between the mean values of intended and achieved depth after surgery for the three locations measured (Wilcoxon signed-rank, P < .05), whereas there were no significant differences in the femtosecond laser group. In the manual group, the proximal part of the stromal tunnel was significantly shallower (−40.87 ± 69.03 μm) than the central (−25.54 ± 71.00 μm) and distal (−26.52 ± 73.22 μm) parts (Friedman test, P < .05). CONCLUSIONS: ICRS implantation assisted by a femtosecond laser provides a more precise procedure considering dissection depth when compared with the manual dissection technique. Such an advantage may provide more predictable clinical results and safer procedures with the femtosecond laser.